Controlled Heat and Humidity-Based Treatment for the Reuse of Personal Protective Equipment: A Pragmatic Proof-of-Concept to Address the Mass Shortage of Surgical Masks and N95/FFP2 Respirators and to Prevent the SARS-CoV2 Transmission - Bernard, Louis; Desoubeaux, Guillaume; Bodier-Montagutelli, Elsa; Pardessus, Jeoffrey; Brea, Déborah; Allimonnier, Laurine; Eymieux, Sébastien; Raynal, Pierre-Ivan; Vasseur, Virginie; Vecellio, Laurent; Mathé, Ludovic; Guillon, Antoine; et al. (Frontiers in Medicine, 2020)
Background: The COVID-19 pandemic has led to an unprecedented shortage of healthcare resources, primarily personal protective equipment like surgical masks and N95 / filtering face-piece (FFP) 2 respirators. Objective: Re-use of surgical masks and N95/FFP2 respirators may circumvent the supply chain constraints, and thus overcome mass shortage. Methods, design, setting and measurement: Herein, we tested the effects of dry- and moist-air controlled heating treatment on structure and chemic integrity, decontamination yield and filtration performance of surgical masks and FFP2 respirators. Results: We found that a treatment in climate chamber at 70°C during one hour with 75% humidity rate was adequate for enabling substantial decontamination of both respiratory viruses, oropharyngeal bacteria and surrogate animal coronaviruses, while maintaining a satisfying filtering capacity. Limitations: Further studies are now required to confirm the feasibility of the whole process during the routine practice. Conclusion: Our findings provide compelling evidence for the recycling of pre-used surgical masks and N95/FFP2 respirators in case of imminent mass shortfall.